Legal and Regulatory Challenges of BIM in Malaysian Construction Law (Architecture Image Studies, 2025)
Building Information Modelling (BIM) is increasingly recognized as a transformative technology in the global construction industry, enabling enhanced project visualization, improved collaboration, and greater accuracy in design and execution. However, the adoption of BIM in Malaysia's construction sector is accompanied by a complex array of legal and regulatory challenges. This study critically examines these challenges, focusing on key areas such as intellectual property rights, data ownership, contract management, and the integration of BIM within existing legal frameworks and construction regulations in Malaysia. The research delves into the implications of BIM on contract formation, dispute resolution, and liability issues, considering the traditional legal structures that may not fully accommodate BIM's collaborative and data-intensive nature. Additionally, the study explores the regulatory environment, assessing how current laws and regulations align with or hinder the adoption of BIM. Through a combination of legal analysis and case studies, this research identifies gaps and proposes recommendations for legal reforms and regulatory adjustments necessary to support the widespread implementation of BIM in Malaysia. The findings provide valuable insights for policymakers, legal practitioners, and construction professionals, guiding them towards a more robust legal framework that facilitates the effective and legally sound integration of BIM into the Malaysian construction industry.